Model Penyusunan Analisis Standar Belanja Kabupaten Kudus Dalam Menunjang Proses Perencanaan, Penganggaran, dan Pengawasan APBD - Sumiati, Siti; Apriyanti, Hani Werdi; Fuad, Khoirul (Lembaga Riset dan Inovasi Al-Matani, 2021)
Local governments need to develop a Standard Expenditure Analysis (ASB) system as mandated in laws and regulations in order to create an effective and efficient budget. It is very important for local governments to provide clarity in determining the time unit and number of units used in activities so that there is uniformity so that the preparation of the Standard Expenditure Analysis is more precise. The basis for preparing the Standard Expenditure Analysis (ASB) should not only look at one year in order to obtain a better ASB model in predicting total expenditure. This study develops an ASB model that can be used by the Kudus Regency Government Keywords : Standard Expenditure Analysis, Budgeting, Kudus